EDUCATIONAL PLATFORMS AS OPTIMAL TOOLS FOR FOSTERING STUDENTS’ KNOWLEDGE ACQISITION - Shakhakimova , Mavjuda Tashpolatovna (Innovative Development in Educational Activities, 2023)
In the contemporary era, technology has assumed a pivotal role in societal functioning, thereby necessitating its integration within the realm of education. Wide range of educational platforms both synchronous and asynchronous have emerged as an essential instrument in facilitating the learning process, offering novel avenues for student development and knowledge acquisition. This article seeks to examine the primary facets of educational platforms utilization in educational contexts, alongside an exploration of their associated benefits and drawbacks.